Using Storyboard as Transmedia to Improve Students' Speaking Ability of 11th Grade MAN 4 Bone - Nahdaniar; Ul Haq, Muhammad Zia; Sangkala, Ismail; Firman (FKIP Unismuh Makassar, 2022)
This study aims to improve the students speaking‟ ability through storyboard as transmedia. This research used true-experimental research. It consisted of three steps, they were pre-test, treatment, and post-test. There were 64 students of MAN 4 Bone involved in this research. The test was an oral test which consisted of three pictures for pre-test and post-test.The findings indicated that using storyboard as transmedia is significant in improving students‟ speaking ability. This was proven by the mean score of Pre- Test and Post-Test between experimental group and control group. The mean score of experimental before and after treatment (45.48 became 73.06) and in control group before and after treatment (45.45 became 63.93) with percentage improvement of experimental group (60%) and control group (40%). Moreover, the findings revealed that P-value score was (0.000) with the level significance 5% (0.05). It can conclude that p-value (0.000) < sig α = (0.05,5%). Thus, it proved that using Storyboard as transmedia Improve Students‟ Speaking Ability of 11th Grade MAN 4 Bone.